Bulk factor characterization of heated debulked autoclave and out-of-autoclave carbon fibre prepregs. (15th August 2021) - Liu, D.S.-C.; Hubert, P.
Abstract: Tow impregnation during cure causes change in the laminate thickness, thus bulk factor, which causes variation in prepreg air permeability and large thickness deviations around corners. A noncontact eddy current thickness sensor monitored the laminate thickness throughout debulk and cure in an oven. Bulk factor values averaged to 1.1 for materials intended for autoclave use and 1.2 for out-of-autoclave, where a lower number is ideal for complex geometries. A heated debulk (HD) at around 48 °C for 2 h resulted in similar bulk factor values as a 16-h room temperature debulk (RTD), suggesting that this shorter cycle can be used as a replacement, resulting in a 26–71% cycle time reduction. For these thick sixteen ply laminates, up to six percent and five percent pore area can be expected of laminates processed RTD and HD, respectively. The highest short beam strength was achieved by a plain weave material intended for out-of-autoclave processing and lowest pore area was achieved by a 5-harness material intended for autoclave processing.